Analysis Of Factors That Influence The Movement Of Dow Jones Industrial Average Using The Multiple Regression Method. - Chuen, Tong Yeah (2003)
Analysing the stock markets can be an arduous task due to the sheer size and complexity of today's stock markets. This research study examines the relationships between four macroeconomic variables and stock prices for the case of United States of America(US) using the standard and universally accepted multiple regression method.